2012
DOI: 10.1002/app.38041
|View full text |Cite
|
Sign up to set email alerts
|

Study of viscoelastic properties of nanocomposites of SiO2–acrylonitrile–butadiene–styrene

Abstract: Nanocomposites of acrylonitrile-butadiene-styrene (ABS) and nanosilica with different nanoparticle sizes and various loadings are prepared. Rheological experiments such as frequency sweep, strain sweep, and rotational test are performed to investigate the influence of nanoparticle loading and size on the viscoelastic properties of the nanocomposites. The results show that nanocomposites with higher filler loading and smaller particle size have both higher storage and loss moduli. Moreover, the results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
(40 reference statements)
1
15
0
Order By: Relevance
“…Many researchers have attempted to understand the relationship between morphological and property changes within the microstructure of rubber material [43], especially with a failure mechanism of elastomer, by using several traditional test methods, including the tensile test, strain-stress relation and compression measurements [44][45][46]. Mooney-Rivlin's equation is usually used to evaluate the property-structure relationship of material by analyzing the tensile stress-strain curves of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have attempted to understand the relationship between morphological and property changes within the microstructure of rubber material [43], especially with a failure mechanism of elastomer, by using several traditional test methods, including the tensile test, strain-stress relation and compression measurements [44][45][46]. Mooney-Rivlin's equation is usually used to evaluate the property-structure relationship of material by analyzing the tensile stress-strain curves of materials.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of various nanoparticles such as silicate layers (clays), carbon nanotubes, silica (SiO 2 ), and calcium carbonate on polymer matrixes have been evaluated in different reports . These studies have tried to understand the relations between the nanostructure and behavior of nanocomposites, which will provide much information for the design and development of advanced materials.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of nanotechnology suggested that the nanoparticles incorporated in polymer matrixes can introduce a revolution in polymer science and technology. Nanoparticles have been extensively used in polymer matrix as reinforcement, due to several favorable properties that they induce compared to micro‐fillers such as the high levels of stiffness and surface area at very low content . In the recent years, polymer nanocomposites as cheap, nontoxic, easy‐produced, high thermal resistant and strong materials show many applications in different fields.…”
Section: Introductionmentioning
confidence: 99%